Qualidade do creme de leite artesanal no semiárido nordestino - Medeiros, Dayse Ariane Soares (Universidade Federal Rural do Semi-Árido, 2017)
The handmade cream is a product of great acceptance in the Brazilian northeast, however, because it is a handmade cream , it offers risks to consumer’s health, because the most of manipulators don’t know the good practices by manufacturing. The aim of this study was to evalue the quality of handmade cream, better known as Backwoods’ cream, through microbiological, physicochemical and molecular analysis. The microbiological analysis were performed on the presence of aerobic mesophilic bacteria, coliforms at 35º and 45º and Staphylococcus coagulase positive. Physicochemical analysis evaluated acidity and moisture content. Molecular analysis was done using the multiplex PCR technique. The results showed that the handmade cream presents inferior quality to that required by the current legislation, because when considering all the microorganisms surveyed, out of 30 samples analyzed, only 1 was fit for human consumption. PCR identified that 29 samples of coagulase positive Staphylococcus was S. aureus. As for the physical-chemical analysis, concerning to the acidity, 27 samples were above the limit recommended by the legislation and 40% were above the established limit in relation to humidity. Therefore, for this product it is necessary to adopt good manufacturing practices and the pasteurization of the milk used in an adequate way, with the objective of guaranteeing hygienic-sanitary quality in order to minimize the risks to human health.
Monografia
Keywords: Creme de leite; Doenças veiculadas por alimentos; Qualidade microbiológica; Milk cream; Foodborne diseases; Microbiological quality; CIENCIAS AGRARIAS::MEDICINA VETERINARIA